(Neo-)Kantian Foundation of Foundations: The Göttingen Case - Peckhaus, Volker (New Perspectives on Neo-Kantianism and the Sciences)

Die Neuformierung der Mathematischen Logik im Nachkriegsdeutschland - Peckhaus, Volker (Geschichte der Tagungen am MFO, 1944 bis 1960er Jahre)

Fraenkel, Abraham A. - Peckhaus, Volker (Neue Deutsche Biographie Deutschland Online)

Kritische Mathematik und die Axiomatik Hilberts - Peckhaus, Volker (Der Geist der kritischen Schule. Kantisches Denken in der Tradition von Jakob Friedrich Fries und Leonard Nelson im 20. Jahrhundert: Wirkungen und Aktualität)

Leibniz’s Influence on 19th Century Logic - Peckhaus, Volker (The Stanford Encyclopedia of Philosophy, first published Sep 4, 2009, substantive revision Feb 2, 2024)

Zermelo - Peckhaus, Volker (Neue Deutsche Biographie, Bd. 28: Wettstein - Zwoch)

Leibniz, Gottfried Wilhelm, General Inquiries on the Analysis of Notions and Truths, edited with an English translation by Massimo Mugnai, Oxford University Press: Oxford 2021 (BSHP New Texts in the History of Philosophy) - Peckhaus, Volker (Mathematical Reviews, MR457231)

Tschirk, Wolfgang. "Vom Universum des Denkens. Eine Geistesgeschichte der Logik". Springer: Berlin 2022, xvii, 117 S. - Peckhaus , Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Kant and the Role(s) of Doctrines of Methods (Journal of Transcendental Philosophy)

Your Smartphone Is Watching You - Eine technikkritische Untersuchung der menschlichen Freiheit und Antiquiertheit im Zeitalter der Digitaltechnologie - Mac Award, Daria-Leona

What is AI Ethics? Ethics as means of self-regulation and the need for critical reflection - Alpsancar, Suzana (International Conference on Computer Ethics 2023)

Bolzano, Bernard: Briefe an Michael Josef Fesl 1837–1840. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1512.01036)

Wolfram, Stephen. Dropping in on Gottfried Leibniz. In: Unravelling Complexity: The Life and Work of Gregory Chaitin, hg. v. Francisco Antonio Doria und Shyam Wuppuluri, World Scientific: Hackensack, NJ 2020, 49–81 - Peckhaus, Volker (Mathematical Reviews MR4450759)

Bolzano, Bernard. Briefe an Michael Josef Fesl 1841–1845. hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2022 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.4). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete ZBl 1512.01037)

Wolfgang Tschirk: Vom Universum des Denkens. Eine Geistesgeschichte der Logik. Springer: Berlin 2022 - Peckhaus, Volker (Mathematische Semesterberichte)

Ernst Schröder’s Algebra of Logic and the ‘Logic of the Ancient - Peckhaus, Volker (Aristotle’s Syllogism and the Creation of Modern Logic: Between Tradition and Innovation, 1820s–1930s (Bloomsbury Studies in the Aristotelian Tradition))

Nakano, Anderson: On Ramsey’s Reason to Amend Principia Mathematica’s Logicism and Wittgenstein’s Reaction, Synthese 199 (2021), 2629–2646. - Peckhaus, Volker (Mathematical Reviews MR4341825)

Schappacher, Norbert. Framing Global Mathematics. The International Mathematical Union between Theorems and Politics, Springer: Cham 2022 - Peckhaus, Volker (Mathematical Reviews MR4461006)

Aranda, Victor. Completeness: From Husserl to Carnap. Logica Universalis 16 (2022), 57–83 - Peckhaus, Volker (Mathematical Reviews MR4451488)

Floyd, Juliet und Felix Mühlhölzer, Wittgenstein’s Annotations to Hardy’s Course of Pure Mathematics. An Investigation of Wittgenstein’s Non-Extensionalist Understanding of the Real Numbers, Springer: Cham 2020 (Nordic Wittgenstein Studies, 7). - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07214204)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 6: Taschennotizbücher1931–32. Anmerkungen, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2022, xiii, 192 S. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07469681)

Hogan, Desmond, “Kant and the Character of Mathematical Inference”, in: Carl Posy et al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 126–154 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1570.01020)

Schlimm, Dirk, "Pasch’s Empiricism as Methodological Structuralism." In: Erich H. Reck und Georg Schiemer (eds.), The Prehistory of Mathematical Structuralism, Oxford: University Press 2020, 88–105 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.01017)

Bellomo, Anna und Guillaume Massas, Bolzano’s Mathematical Infinite. The Review of Symbolic Logic 16, No. 1 (2023), 59–113 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1515.01010)

Tschirk, Wolfgang, Vom Universum des Denkens. Eine Geistesgeschichte der Logik, Springer: Berlin 2022 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.03007)

Herrmann, Kay (Hg.), Grete Henry-Hermann: Philosophie – Mathematik – Quantenmechanik. Texte zur Naturphilosophie und Erkenntnistheorie, mathematisch-physikalische Beiträge sowie ausgewählte Korrespondenz aus den Jahren 1925 bis 1982. Springer VS: Wiesbaden 2019, xv + 664 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1506.01002)

Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Leibniz, Zeitschrift für Didaktik der Philosophie und Ethik

Kants kategorischer Imperativ im sprachsensiblen Philosophieunterricht. Sapere Aude – Habe Mut, dich Primärquellen zu bedienen. (gekürzt) - Albus, Vanessa; Jost, Leif Marvin (Textarbeit im Philosophie- und Ethikunterricht)

Humanismus und Philosophieunterricht - Albus, Vanessa (Humanität als religionspädagogisches und -didaktisches Leitmotiv)

Leibniz. Ein Rationalist im Kanon des Philosophieunterrichts - Albus, Vanessa; Blank, Andreas (ZDPE)

Barbara Schmitz: Was ist ein lebenswertes Leben? Philosophische und biographische Zugänge. Stuttgart Reclam 2022 - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,2: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2023, xv, 229–475 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete, Zbl. 1527.01035)

Du Châtelet et la tradition critique de la Bible. De la ‘philofolie’ aux Examens - Hagengruber, Ruth Edith (La Lettre clandestine n° 30: Émilie Du Châtelet et la littérature clandestine. Moreau, P.F. & Seguin, M.S. (Eds.). Paris)

Die „dritte Wissensdimension“. Eine Epistemologie für eine neue Wissenswelt - Hagengruber, Ruth Edith (Sitzungsberichte der Leibniz-Sozietät der Wissenschaften 150/151, Jahrgang 2022: „Cyberscience – Wissenschaftsforschung und Informatik. Digitale Medien und die Zukunft der Kultur wissenschaftlicher Tätigkeit. Arbeitskreis „Emergente Systeme/Informatik und Gesellschaft“ der Leibniz-Sozietät der Wissenschaften zu Berlin in Kooperation mit der Gesellschaft für Wissenschaftsforschung“)

Du Châtelet and Kant: Claiming the Renewal of Philosophy - Hagengruber, Ruth Edith (Époque Émilienne)
n 1789, Eberhard repudiated Kant’s claim expressed in the first edition of his Critique of Pure Reason to have delivered a new, namely transcendental turn in philosophy, as he was able to retrace our cognition to the origin of phenomena instead of delivering a “merely logical deduction”. Eberhard holds that there was nothing new, but all delivered in Leibniz and Wolff; to prove his claim he refers to a quote from Du Châtelet, taken from a paragraph where she determines the right understanding as to be able “to penetrate to the origin of phenomena”. This paper brings Du Châtelet into discourse with Kant via this Eberhard quote. In its first part, it investigates the use of her quote in the Kant-Eberhard controversy. The second part serves to ground the quote in Du Châtelet’s epistemology. It lays out how to understand Du Châtelet’s claim to penetrate to the origin of phenomena. Du Châtelet’s claim to have renewed philosophy must be taken seriously, and it is helpful for rethinking the German philosophical development from the rationalists to Kant through including Du Châtelet’s theory of cognition.
Keywords: Émilie Du Châtelet; History of Science; Newton; Kant; Eberhard; Wolff; Leibniz

Époque Émilienne
Keywords: Émilie Du Châtelet; History of Science; Kant; Newton; Maupertuis; Voltaire

Language in the Age of Mechanical Reproduction - Thomas, Sven (Technology and Language)

Luna, Laureano. “Strengthening the Russellian Argument Against Abolutely Unrestricted Quantification”. Synthese 200 (2022), No. 3, Paper No. 182, 13 pp - Peckhaus, Volker (Mathematical Reviews)

Coquand, Thierry, “Lorenzen and Constructive Mathematics”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 48–61. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1490.03001)

De Mol, Liesbeth / Bullynck, Maarten, “Making the History of Computing. The History of Computing in the History of Technology and the History of Mathematics”, In: Revue de Synthèse (7) 139 (2018) - Peckhaus, Volker (Mathematical Reviews MR4162129)

Scholz, Heinrich - Peckhaus, Volker (Stanford Encyclopedia of Philosophy)

Neuwirth, Stefan, “Lorenzen’s Reshaping of Krull’s Fundamentalsatz for Integral Domains (1938–1953)”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 143–183. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1484.01013)

Warren, Daniel, "Kant on Mathematics and the Metaphysics of Corporal Nature. The Role of the Infinitesimal”, in: Carl Posy et. al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 66–82 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1492.01011)

Antos, Carolin, “Conceptions of Infinity and Set in Lorenzen’s Operationist System”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 23–46. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1494.03011)

Fermüller, Christian G., "Connecting Sequent Calculi with Lorenzen-Style Dialogue Games", in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51) 143–183 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1490.03014)

Tait, W.W., “Kant on Number”, in: Carl Posy et. al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 267–291 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1495.01012)

Stuhlmann-Laeisz, Gottlob Freges "Grundgesetze der Arithmetik". Ein Kommentar des Vorworts, des Nachworts und der einleitenden Paragrafen, mentis Verlag: Paderborn 2020 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1481.01035)

Nietzsche, Zeitschrift für Didaktik der Philosophie und Ethik

Arbeit, Zeitschrift für Didaktik der Philosophie und Ethik

Mein Stl ist ein Tanz. Nietzsches Über Wahrheit und Lüge im außermoralischen Sinne im sprachsensiblen Unterricht - Albus, Vanessa (ZDPE)

Friedrich Nietzsche. Zur philosophiedidaktischen Kanonisierung eines vieldeutigen Werks - Albus, Vanessa; Glitza, Ralf (ZDPE)

Leibgebundenes Philosophieren in Arbeit und Muße am Sonntag des Lebens - Albus, Vanessa (ZDPE)

Blütenlese, Getreideernte oder Baumfällung? Untersuchungen zum kanonorientierten und sprachsensiblen Philosophieunterricht mit Ganzschriften - Albus, Vanessa (Ganzschriften im Philosophie- und Ethikunterricht. Anachronismus in Zeiten der Digitalisierung oder Gegengewicht zur Häppchenkultur?)

Werner Stegmaier: Formen philosophischer Shriften. Zur Einführung. Hamburg: Junius 2021. 288 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Christian Thiel, Fregeana. Zwölf Studien über Freges Logik
XII + 247 S. Rezension: Dókos. Revista filosófica 31–32 (2023), 275–281 (J. Padilla Gálvez)

Kovač, Srećko, “Logical Foundations and Kant’s Principles of Formal Logic”, History and Philosophy of Logic 40 (2020) - Peckhaus, Volker (Mathematical Reviews [4053233])

Technikphilosophie - Peckhaus, Volker (Staatslexikon. Recht, Wirtschaft, Gesellschaft, Bd. 5: Schule - Virtuelle Realität)

Bolzano, Bernard, "Briefe an Michael Josef Fesl 1831–1836", hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2020 (Bernard Bolzano-Gesamtausgabe. Reihe III: Briefwechsel. Bd. 2.2) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Negrepontis, Stelios, “Plato on Geometry and the Geometers”, in: S.G. Dani et al. (eds.), Geometry in History, Cham: Springer 2019, 1–88 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Fan, Zhao, “Hobson’s Conception of Definable Numbers”, In: History and Philosophy of Logic 41 (2020) - Peckhaus, Volker (Mathematical Reviews)

Vlasáková, Marta, “Logic and Sets”, In: Logic and Logical Philosophy 29 (2020) - Peckhaus, Volker (Mathematical Reviews)

“Mehr wert als tausend Männer” – Luise Adelgunde Victorie Kulmus Gottsched und die wahre Minerva - Hagengruber, Ruth (Musikwissenschaft der Vielfalt. Festschrift für Rebecca Grotjahn zum 60. Geburtstag)

Out of the Box – into the Green and the Blue - Hagengruber, Ruth (Philosophisches Jahrbuch 128. Jahrgang I/2021)

Philosophinnen an die Macht - Hagengruber, Ruth (Female Recruiting Report (3))

Ökonomie, Technik, Umwelt: Die Zukunft bestimmen, während wir die Vergangenheit überdenken: Defining the Future – Rethinking the Past - Hagengruber, Ruth (Konsens)

Vizepräsidentin a.D. des DAB, Prof. Dr. Ulrike Detmers verleiht zum 20. Mal den von ihr ins Leben gerufenen Preis‚ Managerin des Jahres - Hagengruber, Ruth (Konsens)

Der Elisabeth-von-Böhmen-Preis zur Erforschung der Geschichte der Philosophinnen wird zum dritten Mal verliehen - Hagengruber, Ruth (Konsens)

Frauen aus aller Frauen Länder gestalten die Zukunft Deutschlands. Jahrestagung des DAB am 30. April 2021 - Hagengruber, Ruth (Konsens)

Women Philosophers from the Renaissance to the Enlightenment
This collection of essays presents new work on women’s contribution to philosophy between the Renaissance and the mid-eighteenth century. They bring a new perspective to the history of philosophy, by highlighting women’s contributions to philosophy and testifying to the rich history of women’s thought in this period. By showing that women were active in many branches of philosophy (metaphysics, science, political philosophy cosmology, ontology, epistemology) the book testifies to the rich history of women’s thought across Europe in this period. The scope of the collection is international, both in terms of the philosophers represented and the contributors themselves from Britain and North America, but also from continental Europe and from as far afield as Australia and Brazil. The philosophers discussed here include both figures who have recently come to be better known (Elisabeth of Bohemia, Anne Conway, Mary Astell, Catharine Trotter Cockburn, Emilie du Châtelet), and less familiar figures (Moderata Fonte, Lucrezia Marinella Arcangela Tarabotti, Tullia d’Aragona, Madame Deshoulières, Madame de Sablé, Angélique de Saint-Jean Arnauld d’Andilly, Olivia Sabuco, Susanna Newcome). The chapters in this book were originally published as a special issue of the British Journal for the History of Philosophy.
Keywords: History of Women Philosophers; Methodology; History of Philosophy; Women's Studies; Gender History

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)

Der Deutsche Akademikerinnenbund ist Mitglied der Europäischen Bewegung Deutschland (EBD) - Hagengruber, Ruth Edith (Konsens (2021), 9)

Center for the History of Women Philosophers and Scientists Documentation 2016-2019 (Version 1)

The Paris Ms Fr. 12265. A Critical and Historical Online Edition. https://historyofwomenphilosophers.org/dcpm/ (2021-2022)

Du Châtelet, Émilie (1706–1749) - Hagengruber, Ruth (Encyclopedia of Early Modern Philosophy and the Sciences)
Of the many outstanding female philosophers of the European Enlightenment, Emilie Du Châtelet excelled as a physicist, a philosopher, and a mathematician, as well as a Bible critic. She was famous in her lifetime and was not completely forgotten thereafter. Among her admirers, correspondents and friends were the most acknowledged scholars of her time, including Voltaire, Clairault, Maupertuis, Diderot, Helvetius, La Mettrie, Buffon, Christian Wolff, Leonard Euler, and Johann II Bernoulli. Her philosophical work enjoyed high reputation and her opus magnum, the Institutions physiques, was translated into Italian and German and proved her to be an intellectual of European stature. Its defense of living forces and its implied forecast into dynamics as well as her methodological grounding of scientific knowledge as hypothetical, impacted philosophy and science. Reality must by nature escape us. What we perceive are phenomena. Du Châtelet explains the function of space and time to trace us back to the origin of phenomena. Her influence on Kant is evident. Next to her writings in physics, mathematics, philosophy, language, and logic, she contributed to morality and ethics. Du Châtelet left an opus of quite systematic breadth. This impressive publishing activity excels in the amount of its scientific and philosophical production to which a vast collection of manuscripts must be added.She argued against prejudice and idolatry in philosophy and science. Science is a cooperative undertaking over history and beyond nations. Her moral writings align with ideas of the French materialists. Du Châtelet translated and commented on Newton’s Principia, preparing thus the fertile soil of the generation of physicists to come in France.
Keywords: aura Bassi Luise Gottsched Immanuel Kant Dourtous de Mairan Johann II Bernoulli Algarotti Buffon d’Alembert La Mettrie Principle of contradiction Hypotheses Enlightenment Leibniz-Clarke Correspondence Living forces Dead forces; happiness Space Imaginary beings Monads Epicurus Ethics Women philosophers Newton’s laws Principia Motion inertia Active force Vis viva Vis mortua Hypothetic reasoning Hypotheses; a priori principles; Experience; Dead forces; Living forces; Energy Dynamics

Women in Early Modern Philosophy and Science: An Introduction - Hagengruber, Ruth Edith (Encyclopedia of Early Modern Philosophy and the Sciences)
Essential ideas significantly connected to humanism, Renaissance, and early modern philosophy stem from women’s pens. The supportive role of women in the early modern period has hardly been recognized up to today. The relevant issues women have contributed to range from commentaries on and critiques of the Bible, and their demands for equality and the critique of political institutions, topics that became eminent enhancers of political and societal change in the relevant period of early modern philosophy, to enlightenment philosophy.

Simmels Abhandlungen zu Kant - Luft, Sebastian (Simmel-Handbuch)

Cassirer’s Children, Special Topics Issue
Keywords: General Medicine

Wilhelm Windelband. Präludien

»Wir hören Dich nicht, schalte bitte Dein Mikro an ! « Einige Gedanken zur digitalen Lehre in der Pandemie. - Luft, Sebastian
Auch in diesem Semester finden Veranstaltungen im Fach Philosophie an den meisten Universitäten vor allem online statt; die Pandemie-Lage lässt eine Öffnung der Unis für Präsenzveranstaltungen kaum zu. Die folgenden Überlegungen hat Sebastian Luft, Professor an der Marquette University in Milwaukee/WI, aus aktuellem Anlass verfasst. 2019 erschien sein Buch »Philosophie lehren« zur philosophischen Hochschuldidaktik. Der folgende Text bietet eine aktuelle Ergänzung zur dortigen Handreichung für die philosophische Lehre.

In Amerika promovieren? Hinweise von Sebastian Luft - Luft, Sebastian (Information Philosophie)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 7: Synopse der Manuskriptbände I bis IV, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2020 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1472.01028)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 9: Philosophische Bemerkungen, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2020 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1475.00016)

Kulturelle Phänomene und philosophische Herausforderungen. Impulse für Bildungsprozesse in Theorie und Praxis

Ehre, Zeitschrift für Didaktik der Philosophie und Ethik

Auf Spurensuche einer interkulturellen Philosophiedidaktik - Albus, Vanessa (Kulturelle Phänomene und philosophische Herausforderungen. Impulse für Bildungsprozesse in Theorie und Praxis)

Einleitung - Albus, Vanessa (Kulturelle Phänomene und philosophische Herausforderungen. Impulse für Bildungsprozesse in Theorie und Praxis)

Sprachsensibler Philosophieunterricht mit digitalen Medien. Eine Diskussion über PhiloWelt - Albus, Vanessa; Yetisen, Gökhan (ZDPE)

Ehre – ubiquitär und dennoch obsolet? Betrachtungen aus philosophiedidaktischer Perspektive - Albus, Vanessa (ZDPE)

Logik - Peckhaus, Volker (Gottfried Wilhelm Leibniz. Rezeption, Forschung, Ausblick)

Kurt Gödel, Collected Works, Vol. IV: Correspondence A–G, Vol. V: Correspondence H. Ed. by Solomon Feferman et al. Oxford: Clarendon Press 2003 - Peckhaus, Volker (Historia Mathematica)

The Mathematical World of Charles L. Dodgson (Lewis Carroll). Edited by Robin Wilson and Amirouche Moktefi. Oxford University Press: Oxford 2019 - Peckhaus, Volker (British Journal for the History of Mathematics)

The Continued Exercise of Reason. Public Addresses by George Boole. Edited by Brendan Dooley. The MIT Press: Cambridge, Mass. and London, Engl. 2018 - Peckhaus, Volker (Isis)

Grußwort - Peckhaus, Volker (Verleihung der Ehrendoktorwürde an Maria von Welser durch die Fakultät für Kulturwissenschaften der Universität Paderborn am 14. November 2019)

van Atten, Mark, "Essays on Gödel’s Reception of Leibniz, Husserl, Brouwer", Springer: Cham u.a. 2015 (Logic, Epistemology, and the Unity of Science, 35) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Jost, Jürgen, "Leibniz und die moderne Naturwissenschaft", Springer: Berlin 2019 (Wissenschaft und Philosophie) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Edwards-McKie, Susan, "On the infinite, in-potentia: discovery of the hidden revision of Philosophical Investigations and its relation to TS 209 through the eyes of Wittgenstein's Mathematics", in: Mras, Gabriele M. et al. (eds.), Philosophy of logic and mathematics. Proceedings of the 41. international Ludwig Wittgenstein Symposium, de Gruyter: Berlin 2019, 441-456 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ramharter, Esther, "Der Status mathematischer und religiöser Sätze bei Wittgenstein", in: Mras, Gabriele M et al. (eds.), Philosophy of logic and mathematics. Proceedings of the 41. international Ludwig Wittgenstein Symposium, de Gruyter: Berlin 2019, 485-497 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Mathematische Schriften 1804–1810", hg. v. Steve Russ und Edgar Morscher, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2020 (Bernard Bolzano-Gesamtausgabe. Reihe I: Schriften. Bd. 1) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Coury, Aline Germano Foseca; Vilela, Denise Silva, “Russell’s Paradox: A Historical Study About the Paradox in Frege’s Theories”, In: Revista Brasileira de História da Mathématica 19, No. 37, 95–116 - Peckhaus, Volker (Mathematical Reviews)